2022
DOI: 10.1123/jsr.2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Application of Eccentric Force Using Different Rotary Inertia Devices May Influence the Treatment of Tendinopathy

Abstract: High intraset variability has been considered as a potential aid in the treatment of tendinopathy by producing forces in variable and unpredictable contexts that allow the athlete to return to sport pain free. The aim of this study was to compare the intraset variability in force profiles between different rotational inertia devices (RIDs) during concentric and eccentric (ECC) phases of movement and between different moments of inertia. Thirty-nine men performed a half-squat incremental test on 2 different RID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, increasing the variability of the load to the training session did not evoke any additional changes to CMJ height. Recently, it has been reported that RIDs provide high levels of variability in force and velocity during the exertion of the exercise (Moras et al, 2018; Nunez et al, 2021). Therefore, it is possible that half‐squat RIDs offer a high level of variability per se, and increasing this level of variability will not add benefits to CMJ outcomes, but there are no undesired adaptations either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing the variability of the load to the training session did not evoke any additional changes to CMJ height. Recently, it has been reported that RIDs provide high levels of variability in force and velocity during the exertion of the exercise (Moras et al, 2018; Nunez et al, 2021). Therefore, it is possible that half‐squat RIDs offer a high level of variability per se, and increasing this level of variability will not add benefits to CMJ outcomes, but there are no undesired adaptations either.…”
Section: Discussionmentioning
confidence: 99%
“…ST with flywheel devices have showed positive adaptation on muscle mass (Maroto‐Izquierdo et al, 2019; Tesch et al, 2004), maximal strength (Maroto‐Izquierdo et al, 2019; Tesch et al, 2004), sprint (De Hoyo, Pozzo, et al, 2015; Gonzalo‐Skok et al, 2017), and power output (Maroto‐Izquierdo et al, 2019; Suchomel et al, 2019). In addition, it has been suggested that RIDs offer higher ECC muscular activation and force production than conventional ST (Norrbrand et al, 2010; Petre et al, 2018) and allows a high variability on force and velocity during the exercise (Nunez et al, 2021). As RIDs guarantee an increase in the variability of the stimulus, it is unknown if increasing the level of variability during ST with RIDs will lead to the aforementioned undesired adaptations.…”
Section: Introductionmentioning
confidence: 99%